UJI STABILITAS KADAR BAHAN KONTROL POOLED SERA PEMERIKSAAN KIMIA KLINIK TERHADAP WAKTU DAN SUHU PENYIMPANAN - Setiawan, Heru; Semendawai, Muhammad Yusuf; Febiyanto, Novian (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
In providing quality assurance for laboratory examinations, it is necessary to ensure quality by examining control materials. Pooled sera was chosen as a control material because the use of commercial control materials is relatively expensive and if the specimens examined are of human origin, it is better to use control materials of human origin as well. The use of pooled sera must be stable over a long period of time. The selection of HDL-Cholesterol and AST parameters is expected to be representative in metabolic and enzymatic examinations. The aim of the research was to determine the stability of pooled sera control materials level in clinical chemistry tests against storage time and temperature. This research is an experimental study, pooled sera were treated at storage time of 0, 1, 2, 3, 7, 14, 28, and 35 days and storage temperature (-5ºC and -20ºC) then HDL-Cholesterol and AST levels were measured repeatedly 3 times each. Data analysis used the repeated measure ANOVA test with 95% confidence level. The results showed that the test for the difference in average HDL-Cholesterol levels for each treatment had a value of p=0.002 < α=0.05, and the test for the difference in average AST levels for each treatment had a value of p=0.081 < α=0, 05. The conclusion of this study is that there is a significant difference between HDL-Cholesterol levels in each treatment (unstable) and there is no significant difference between AST levels in each treatment (stable).